FEATURES OF FUTURE ENGINEERS' FUNDAMENTAL TRAINING IN CRISIS CONDITIONS - Viktor Kaplun; Nina Batechko; Lyudmila Pantaliyenko (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article reveals the features and the role of future engineers' fundamental training, in particular, in crisis conditions. The importance of the fundamental component in engineering training and the didactic purpose of future engineers' mathematical training have been considered. The peculiarities of future engineers' fundamental training in the conditions of online learning and mixed format have been revealed. The main trends of engineering education in pedagogical theory have been highlighted. The article considers future engineers' fundamental training, in particular in mathematics, as the basis for their system thinking formation. Linear and non-linear systems of formation of future engineers' system thinking have been highlighted. The linear system has been singled out against the background of the established educational process of future specialists' training; non-linear - in crisis conditions which are characterized by instability, uncertainty and chaos. A nonlinear model of formation of future engineers' system thinking in the aspect of student's fundamental training has been generated. The experimental part of the study was carried out on the basis of the sample data formalization on the stage of transformation of students' mathematical knowledge - from the elementary course of mathematics to higher education. As a compensation and preservation of mathematical knowledge, it has been proposed to conduct adaptation courses in elementary mathematics, which enable continuity and consistency in assimilation of mathematical knowledge, and therefore contribute to increasing efficiency in formation of future engineers' system thinking.